Development of enhanced air-cooled heat sink arrays - Aw, Janine Kai Ning (Nanyang Technological University, 2021)
This report details the heat transfer performance of conical, sharp-tipped heat sinks. Four different heat sinks are fabricated using SLM and they are subjected to air jet impingement in an enclosed experimental rig. These heat sinks refer to the conventional cone array and three other novel designs that have retained several conical characteristics. The novel design fin consists of two stacked truncated cones. The base truncated cone angle is varied for each design at 60°, 65° and 70°. The novel design is hypothesised to overcome the heat transfer challenges experienced by conventional cone arrays. These challenges include pressure drop caused by impact of fluid on the base plate and clashing of vortices between adjacent cones in the array which results in the loss of fluid momentum. Simulations in Ansys are carried out to investigate the flow effects initiated by the novel heat sinks. The flow visualisations showed that the novel design is capable of augmenting heat transfer within the heat sink by initiating higher velocity circulation within the fins. The flow vectors also display smaller vortices formed at the base of the truncated cone, preventing the occurrence of clashing vortices. The experimentation results show that the truncated cone design can effectively lower pressure drop. Two different nozzle sizes were used in the experimentation. It is found that the 10 mm diameter nozzle results in a dampened heat transfer performance compared to the 15 mm diameter nozzle due to its higher pressure drop. Using the 10 mm diameter nozzle, at lower Re, the 65° truncated cone array is displayed to have the highest Nu of maximum 18.4%, 15.38%, 4.10% greater than the conventional cone, 60° cone and 70° cone, respectively. At higher Re, the 70° cone array has the largest Nu, that is at maximum 6.67%, 11.50% and 22.35% higher than the conventional cone, 65° cone and 60° cone, respectively. These Nu trends follow the theory that lower pressure drop leads to more effective heat transfer. Specifically, the pressure drop of the 65° truncated cone array is at maximum 40% lower than the conventional cone while the 70° truncated cone array is at maximum 30% lower. With the effects of both lower pressure drop and better circulation between the fins, the truncated cone design is determined to have more enhanced heat transfer rates than the conventional cone.